Measuring and Pricing the Risk of Corporate Failures - Mamdouh Medhat (Copenhagen Business School (CBS), 2015)
These writings constitute my PhD dissertation in financial economics. The dissertation consists of three chapters. Each chapter can be read independently of the others, but all three chapters share the dissertation's overall topic: Measuring and pricing the risk of corporate failures. The ability to adequately measure and price the risk of corporate failures is vital for creditors, shareholders, and regulators of financial institutions. Whenever a firm uses debt instruments such as loans or bonds to finance its operations, the firm may fail to meet the debt's contractual obligations. Typically, a failure is in the form of a default on a payment of interest or principle, but can also be a violation of a covenant attached to the debt or a bankruptcy filing by the firm or by the creditors on behalf of the firm. If a firm fails, it may be forced to temporarily or permanently halt its operations, which can entail losses: Creditors may realize a loss on their promised payments, while shareholders may see their entire equity stake wiped out. Therefore, creditors and shareholders need to adequately measure the risk of a failure, so that this risk can be reflected in the prices they are willing to pay—and the returns they require—for holding a firm's financial securities. At the same time, regulators must be able to verify that a financial institution is adequately cushioned against this risk, so that losses do not destabilize an important institution or even the financial system itself.
hdl:10398/9137
Keywords: 650